Pengaruh Nutrisi pada Berbagai Medium Tanam terhadap Pertumbuhan dan Hasil Tanaman Tomat (Lycopersicon esculentum L.) Secara Hidroponik - Sulistiani, Dwi; Ardian, Ardian; Ariani, Erlida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to examine the effect of POC banana skin nutrition and the use of plant medium and to obtain the best combination of treatments on the growth and yield of hydroponic cultivated tomato plants. This research was conducted in Experimental Garden of Agricultural Faculty of Riau University, Pekanbaru from June to October 2017. This study used a complete randomized design (RAL). The first factor is POC nutrients of banana skin with concentrations of: 20 ml.l-1 water, 35 ml.l-1 water, and 50 ml.l-1 water. The second factor is planting medium that is Charcoal husk, Cocopeat and Charcoal husk + cocopeat (with ratio 1: 1). The parameters observed were plant height, stem diameter, flowering age, percentage of flower to fruit, number of fruit crops, age of first harvest, weight per fruit, fruit diameter and fruit weight per plant. Provision of POC banana peel 35 ml.l-1 water in husk charcoal medium to increase the growth of plant height, the percentage of flowers into fruit, the number of fruit crops and the weight of fruit crops. Keywords: nutrition, planting medium, hydroponics